행동이론에 근거한 가임여성 대상 영양교육 프로그램 개발 - 오세영(Se-Young Oh); 김경아(Kyung-A Kim); 유혜은(Hye-Eun You); 정해랑(Hae-Rang Chung) (Korean journal of community nutrition, 2004)
It was well received that well grounded behavioral theories were important in the development of effective nutrition education programs, but there are only a few programs available for Korean women. The objective of this study was to develop nutrition education programs for childbearing-aged women in Korea. Based on the findings of the needs assessment for the program and theoretical backgrounds, we developed behaviorally oriented tailored nutrition education program including motivation (MT), modifying (MD) and maintenance (MA) stages. The key concepts of the stages were motivation promotion for MT, increasing behavioral capabilities for MD, and strengthening self-management and building favorable environmental condition for MA. The education program was intended to be need in individual nutrition counseling, but it could be well used for group education by developing materials using the relevant contents. The primary users of the program were nutrition educators, however it could be also used by clients as needed. The introductory chapter provided dietary assessment tools and nutrition education tips. MT chapter included subjects such as nutritional status screening, costs of inappropriate nutrition and weight management, benefits of eating right, and activities for motivation promotion. MD stage chapter dealt with topics of healthy weight, knowledges and skills for better eating habits and physical activity status, and activities related to setting tailored behavioral objectives. MA stage focused on facilitating self management skills and building helping relationships. Each stage underlined activities using various educational tools in order to promote active participation of the client (s). For better use of this program, it was recommended to conduct program validation study.